Exendin-4 effects on islet volume and number in mouse pancreas (Brazilian Journal of Pharmaceutical Sciences, 2013)
The aim of this study was to evaluate Exendin-4 (EX-4) effects on islet volume and number in the mouse pancreas. Thirty-two healthy adult male NMRI mice were randomly divided into control and experimental groups. EX-4 was injected intraperitoneally (i. p.) at doses of 0.25 (E1 group), 0.5 (E2 group), and 1 µg/kg (E3 group), twice a day for 7 consecutive days. One day after the final injection, the mice were sacrificed, and the pancreas from each animal dissected out, weighed, and fixed in 10% formalin for measurement of pancreas and islet volume, and determination of islet number by stereological assessments. There was a significant increase in the weight of pancreases in the E3 group. Islet and pancreas volumes in E1 and E2 groups were unchanged compared to the control group. The E3 group showed a significant increase in islet and pancreas volume (P < 0.05). There were no significant changes in the total number of islets in all three experimental groups. The results revealed that EX-4 increased pancreas and islet volume in non-diabetic mice. The increased total islet mass is probably caused by islet hypertrophy without the formation of additional islets.